Assessing Short- and Long-Term Repeatability and Stability of Personality in Captive Zebra Finches Using Longitudinal Data - David, Morgan; Auclair, Yannick; Cézilly, Frank (Ethology, 2012)
Assessing behavioural consistency is crucial to understand the evolution of personality traits. In the present study, we examined the short‐ and long‐term repeatability and stability of two unrelated personality traits – exploratory tendencies and struggling rate – using captive female zebra finches ( Taeniopygia guttata). We performed two experimental sessions of behavioural tests with a 7‐mo interval, which represents up to one quarter of a zebra finch's life expectancy. We showed that, overall, exploratory tendencies and struggling rate were significantly repeatable in the short term. However, only exploratory tendencies were repeatable in the long term. We found interindividual differences in short‐term stability of exploratory tendencies, but not struggling rate, providing evidence for differences in intraindividual variability. In the long term, struggling rate significantly decreased between the two experimental sessions, whereas exploratory tendencies remained stable. Finally, the amount of interindividual variation measured at both sessions did not differ. Our results suggest that short‐ and long‐term repeatability and stability of personality may vary between individuals, depending on the behavioural trait under scrutiny. As a consequence, deducing personality from measures realized earlier in a subject's life should be performed with caution. We discuss the implications of inter‐ and intraindividual variation in personality consistency on individual fitness.